Acute Caval Thrombectomy: A Review of Tools, Techniques, and Outcomes for Inferior Vena Cava Thrombosis - Sajan, Abin; Posham, Raghuram; Reis, Stephen; Ahmad, Noor (Seminars in Interventional Radiology, 2025)
Inferior vena cava thrombosis (IVCT) is a rare but severe form of venous thromboembolism, associated with significant risks of pulmonary embolism and post-thrombotic syndrome. While anticoagulation remains the primary treatment, acute caval thrombectomy has emerged as an effective strategy for rapid thrombus resolution in select cases. This review examines the tools, techniques, and outcomes of endovascular interventions, including aspiration and mechanical thrombectomy devices as well as catheter-directed thrombolysis and adjunctive technologies such as intravascular ultrasound and temporary IVC filters. Published retrospective studies show technical success rates of 80 to 100% and vessel patency of 75 to 90% at 6 to 12 months, with low complication rates. Despite promising results, prospective studies are needed to standardize device selection and post-procedural care. This review highlights thrombectomy's role as a first-line option for IVCT, offering rapid, lytic-free clot removal.
Keywords: inferior vena cava thrombosis; caval thrombectomy; aspiration thrombectomy; mechanical thrombectomy; catheter-directed thrombolysis; interventional radiology